Can Gender be a Moderating Variable in Micro Small Medium Enterprises Financial Behavior? A Perspective from Financial Financial Literacy, Financial Attitude, and Income - Sriyono Sriyono; Novita Lailatul Rif’ah (Jurnal Manajemen Bisnis, 2022)
Research aims: This study aims to determine whether gender can moderate the relationship between income and financial literacy, financial attitudes, and financial management behavior in Sidoarjo MSMEs.Design/Methodology/Approach: The study used quantitative methods. The population was all micro, small and medium enterprises registered with the Cooperatives and Small Business Administration. Meanwhile, the sampling technique employed targeted sampling and obtained 164 MSMEs. The analysis technique utilized in this study was path analysis using Smart PLS 3.0. Research findings: This study revealed that gender could moderate financial literacy and attitudes towards financial management behavior in SMEs. However, gender could not affect the income of small business financial management behavior.Theoretical contribution/Originality: Research contributions are crucial for small business actors to overcome bad financial behavior. Through the results of this study, it will be known how MSMEs should improve financial behavior and whether gender differences are considered to still significant in leading a company.Practitioner/Policy implication: The implications of this study are vital; through the results, it can be known how gender roles are against a company. Nevertheless, the limitation of this study is the lack of variables used, so it could not explore gender more broadly.